2019
DOI: 10.1080/13696998.2019.1620752
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare resource utilization and costs associated with venous thromboembolism in cancer patients treated with anticoagulants

Abstract: Objective: The standard of care for cancer-related venous thromboembolism (VTE) has been low molecular weight heparin (LMWH), but oral anticoagulants are also widely prescribed. This study compared VTE-related healthcare resource utilization and costs of cancer patients treated with anticoagulants. Methods: Claims data from Humana Database (January 1, 2013-May 31, 2015) were analyzed. Based on the first anticoagulant received, patients were classified into LMWH, warfarin, or rivaroxaban cohorts. Characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…This is line with findings from a recent study that assessed the VTE-related healthcare costs in patients with cancer, which found that rivaroxaban-treated patients had a significantly lower total VTE-related costs relative to patients treated with LMWH. 33 Although the cost difference between the rivaroxaban and dalteparin cohorts was even greater with $12 004 per patient per year.…”
Section: Discussionmentioning
confidence: 99%
“…This is line with findings from a recent study that assessed the VTE-related healthcare costs in patients with cancer, which found that rivaroxaban-treated patients had a significantly lower total VTE-related costs relative to patients treated with LMWH. 33 Although the cost difference between the rivaroxaban and dalteparin cohorts was even greater with $12 004 per patient per year.…”
Section: Discussionmentioning
confidence: 99%
“…The patients may be suffering from pancreatic cancer, breast cancer, genitourinary cancer, lung cancer, ovarian cancer, gastroesophageal cancer squamous cell carcinoma, adenocarcinoma, and lymphoma [28,[32][33]. In ambulatory patients, rivaroxiban showed a decreased risk of VTE but major bleeding occurred in few cases and in some cases, the reoccurrence of VTE and bleeding increased [23,33]. In primary and metastatic brain cancer, this drug showed more safety than LMWH [34].…”
Section: Use Of Noacs In Different Cancersmentioning
confidence: 99%
“…Randomized controlled trials (RCTs) had demonstrated superior efficacy to vitamin K antagonists in preventing recurrent VTE with similar rates of major bleeding 8,9 . However, long term adherence with subcutaneous LMWH is highly variable, ranging between 19 to 70% 10 , and can be associated with higher healthcare costs compared to other anticoagulants 11 .…”
Section: Introductionmentioning
confidence: 99%